2006
DOI: 10.1002/nbm.1052
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between MRS and DTI in cerebral small vessel disease

Abstract: Cerebral small vessel disease results in lacunar infarcts and cognitive impairment. Diffusion tensor imaging (DTI) demonstrates a reduction in fractional anisotropy and increase in mean diffusivity, which correlates more strongly with cognition than conventional MRI. The underlying pathological basis for these DTI changes is not known. In this study magnetic resonance spectroscopy was used to determine the biochemical basis of these DTI alterations. Twenty-five patients with lacunar stroke and radiological leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…FA provides information on the main direction of diffusion and is therefore likely to be a better indicator of white matter tract disruption (24). Studies in which DTI has been correlated with magnetic resonance spectroscopy have found FA correlated most strongly with N-acetyl aspartate, a marker of neuronal and axonal integrity, consistent with DTI being a measure of axonal damage (9,25). Therefore, this stronger correlation is consistent with white matter tract disruption and secondary corticalsubcortical and cortical-cortical disconnection playing a role in age-related cognitive decline (5).…”
Section: Discussionmentioning
confidence: 90%
“…FA provides information on the main direction of diffusion and is therefore likely to be a better indicator of white matter tract disruption (24). Studies in which DTI has been correlated with magnetic resonance spectroscopy have found FA correlated most strongly with N-acetyl aspartate, a marker of neuronal and axonal integrity, consistent with DTI being a measure of axonal damage (9,25). Therefore, this stronger correlation is consistent with white matter tract disruption and secondary corticalsubcortical and cortical-cortical disconnection playing a role in age-related cognitive decline (5).…”
Section: Discussionmentioning
confidence: 90%
“…15 Percentage lesion volume was determined as a ratio of lesion volume to nonnormalized brain volume.…”
Section: Image Analysis and Postprocessingmentioning
confidence: 99%
“…[6][7][8] This technique allows non-invasive imaging of metabolic changes within brain tissue. Evidence of neuronal or axonal loss and damage can be obtained by measuring N-acetylaspartate (NAA), a marker of neuronal and axonal integrity, viability, activity, and function.…”
Section: Introductionmentioning
confidence: 99%